2005
DOI: 10.1152/japplphysiol.00554.2004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibrillin-1 genotype on the aortic stiffness in men

Abstract: Aortic stiffness is a predictor of cardiovascular mortality. The mechanical properties of the arterial wall depend on the connective tissue framework, with variation in fibrillin-1 and collagen I genes being associated with aortic stiffness and/or pulse pressure elevation. The aim of this study was to investigate whether variation in fibrillin-1 genotype was associated with aortic stiffness in men. The mechanical properties of the abdominal aorta of 79 healthy men (range 28-81 yr) were investigated by ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
5
17
2
1
Order By: Relevance
“…8 The most common genotypes in the present and previous studies were 2/2, 2/3 and 2/4, accounting for 92.2% of the populations studied. [7][8][9][10]18,19 There was no association between FBN1 2/3 compared with the 2/2 and 2/4 genotypes and increased blood pressure in the present study, in accordance with findings from previous studies in health subjects. 10,18 However, a subsample of individuals in the study of Powell et al 18 with pulse pressure > 50 mmHg were found to have an association between the 2/3 genotype and pulse pressure, although there were only a few such subjects in the study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…8 The most common genotypes in the present and previous studies were 2/2, 2/3 and 2/4, accounting for 92.2% of the populations studied. [7][8][9][10]18,19 There was no association between FBN1 2/3 compared with the 2/2 and 2/4 genotypes and increased blood pressure in the present study, in accordance with findings from previous studies in health subjects. 10,18 However, a subsample of individuals in the study of Powell et al 18 with pulse pressure > 50 mmHg were found to have an association between the 2/3 genotype and pulse pressure, although there were only a few such subjects in the study.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in FBN1 cause Marfan syndrome, and mutated FBN1 has been associated with increased aortic stiffness as well as increases in central pulse pressure. 16,17 Several studies have investigated FBN1 genotypes in different populations, and the frequency of the genotypes in the present study is in accordance with what has been reported previously in healthy individuals, 9,10,18 patients with AAA 7,19 and patients with CAD. 8 The most common genotypes in the present and previous studies were 2/2, 2/3 and 2/4, accounting for 92.2% of the populations studied.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6 Fibrillin-1 genotype has also been linked to TAA, dissection, and other aortic abnormalities in patients without Marfan syndrome. [7][8][9][10] Furthermore, a recent genome-wide association study identified a susceptibility locus for sporadic TAA and dissection in a region containing the fibrillin-1 gene. 11 Mutations in fibrillin-1 have been shown to destabilize fibrillin-1 protein, making it more susceptible to proteolytic degradation.…”
mentioning
confidence: 99%